2018
DOI: 10.14349/rlp.2018.v50.n1.6
|View full text |Cite
|
Sign up to set email alerts
|

A Text Mining Approach to the Text Difficulty of Latin American Peace Agreement

Abstract: A peace agreement was recently subjected to a plebiscite as a solution to finish the Colombian armed conflict. With 62.57% of abstention, 18.44% of the Colombian electorate rejected this agreement. This paper aims to propose a methodological approach that shows how to linguistically analyze peace agreements as political products that are acceptable or not according to their text difficulty. Given the socio-political similarities of the armed conflicts of Colombia, Guatemala, and El Salvador, we scrutinized wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The aim of this paper was to analyze the effects that geographic distance has on the economic well-being of Colombian migrants. As it is well-known, Colombia has suffered an internal war of 52 years among different groups of the society including guerrillas, paramilitaries, and government, resulting in six millions of displaced people (Correa et al, 2018). Given the vulnerability of these people, we posited the idea that their economic well-being would be inferior in comparison with other sorts of migrants, and this should be in perspective with the centralization of the country that could affect their decision to leave their homes and possessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this paper was to analyze the effects that geographic distance has on the economic well-being of Colombian migrants. As it is well-known, Colombia has suffered an internal war of 52 years among different groups of the society including guerrillas, paramilitaries, and government, resulting in six millions of displaced people (Correa et al, 2018). Given the vulnerability of these people, we posited the idea that their economic well-being would be inferior in comparison with other sorts of migrants, and this should be in perspective with the centralization of the country that could affect their decision to leave their homes and possessions.…”
Section: Discussionmentioning
confidence: 99%
“…During 52 years Colombia has suffered an armed conflict that produced the forced displacement of six millions of people (Correa et al, 2018). Forced migration implies the movements of internally displaced people by armed conflicts or natural, environmental, chemical or nuclear disasters, famine, or development projects.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that we could only obtain evidence of an indirect effect of reappraisal on aggressive statements against FARC may relate to the characteristics of the texts that were presented to the participants—i.e., excerpts from the peace accord signed between FARC and Colombian government and aggressive statements from national newspapers. For instance, Correa et al (2018) found that linguistic aspects of the Colombian government-FARC peace accord made its legibility very low, which adds to the more general finding that legal and political texts are not easily comprehended by lay persons (Charrow and Charrow, 1979; Jones et al, 2012; Mandic et al, 2012). Pilot testing of the different statements used in the present study was not possible due to the close date established for the referendum on the signed peace accord (less than 2 months), which may have resulted in the moderate levels of internal consistency observed for both sets of statements (α conciliatory = 0.65; α aggressive = 0.68).…”
Section: Discussionmentioning
confidence: 99%
“…Our third hypothesis was that positions regarding forgiveness would be associated with attitudes regarding socio-political issues currently debated in Colombia (Correa, García-Chitiva & García-Vargas, 2018) In particular we expected that participants asserting the always forgive position would be more favorable to the peace dialogs in La Habana, and would be more convinced that Colombian's security strongly depends on the signature of a peace accord than participants asserting the never forgive or hesitant positions.…”
Section: Hypothesesmentioning
confidence: 97%